2023
DOI: 10.9734/ijpss/2023/v35i213940
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Physico-chemical Properties of Soil under Various Land Use Planning of Kanpur Nagar, U.P., India

Abhishek Kumar,
Sanjeev Sharma,
Arpita Soni
et al.

Abstract: A research work conducted during 2020-21 at various land use planning of Kanpur Nagar (U.P.) to evaluate the fertility status of various land use planning on soil physico-chemical characteristics. The 504 representative soil samples with 3 depths viz. 0-15, 15-30 and 30-60 cm soil samples were taken with manually driven post hole auger and processed for soil analysis from different land use planning of Kanpur Nagar. Results revealed that physico-chemical properties viz. Bulk density, pH, Electrical Conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…It was also observed the pH of soil was gradually increased with an increase in dose of different levels of NPK and Zn. Similar result has been recorded by Chandrakar, [18] : Jha et al, [19] .…”
Section: Chemical Properties Of Soil Soil Ph (1:25) W/vsupporting
confidence: 90%
“…It was also observed the pH of soil was gradually increased with an increase in dose of different levels of NPK and Zn. Similar result has been recorded by Chandrakar, [18] : Jha et al, [19] .…”
Section: Chemical Properties Of Soil Soil Ph (1:25) W/vsupporting
confidence: 90%
“…Additionally, it was noted that when the dosage of various NPK and biochar levels grew, the BD of the soil steadily increased as well. Kumar et al [6], Reddy et al, [7] and Bhattacharya et al [8] have all reported similar results.…”
Section: Physical Property a Bulk Density (Mg M -3 ) (Bd)mentioning
confidence: 64%